Implementasi Deteksi Dini Kanker Payudara dan Kanker Leher Rahim dengan Menggunakan Metode CBE dan IVA di Kabupaten Lampung Selatan - Sudarmi Sudarmi; Nurchairina Nurchairina (Politeknik Kesehatan Tanjung Karang, 2017)
Breast cancer and cervical cancer are the highest female cancers in Indonesia. Both of these cancers become one of the main problems in health. From 2007 Up to 2014, the program has been running at 1,986 Puskesmas in 304 districts/ cities located in 34 provinces in Indonesia, including southern Lampung regency. The purpose of this study was to evaluate the implementation of prevention / early detection program of breast cancer and cervical cancer. The research method used is descriptive qualitative, research time July to December 2016. Technique of collecting data using documentation study, interview, observation, and active participation, using protocol research, Data analysis is done by testing the prevalence of data, classify data according to sub focus and Research question, merging of data in matrix or table form and triangulation strategy to describe the result of analysis and research findings. The results of the implementation of early detection of breast cancer and cancers of the womb of Rahim 2016, CBE Implementation 75% according to SOP, Implementation of IVA 86.3% according to SOP and from target 28.138 (20%) WUS only reached 14.821 (52.67%), and found lesions White (Accetowhite) 357 (2.49%) and CBE positive 198 (1.34%). Recommendations addressed to the Health Department, head of Puskesmas and cancer detection operators in the process of cancer detection are expected in accordance with Standard Operating Procedures (SOP) so that the expected program objectives can be achieved.